(untitled) (College of Basic Education Research Journal, 2025)
• Know effect of variable practice schedules accompanied by some educational tools and way followed in learning number of attack skills in basketball on two groups of research. • Preference between control and experimental research groups in learning a number of offensive basketball skills as shown in results of post-test. Researchers assumed that: • There are significant differences between pre- and post-test results of control and experimental group in learning number of offensive skills in basketball and in favor of post-test results. Researchers used experimental method with two equal groups. Research community was (190) male and female students of academic year (2023-2024) . Research sample was (32) freshmen in Physical Education and Sport Sciences Department / College of Basic Education / University of Mosul in academic year2023/2024. Two independent variables were given to two classrooms in a random way using simple random draw, each group had (16) students. Control group studied traditionally depending on their professor while experimental group studied according to variable practice schedules accompanied by various educational tools. Educational curriculum contained (16) educational unit so that each group took (8) units. Time of each educational unit is (90) minutes. Researchers concluded that: Experimental group that used variable practice schedules accompanied by various educational tools out-performed control group in learning number of offensive skills in basketball in post-test results and all other skills.